Growth Responses of Sugarcane (Saccharum officinarum L.) Ratoon Cane to Vegetative Phase and Sugarcane Formula Fertilizer in Inceptisol - Pradana, Yogi Wahyu; Putra, Eka Tarwaca Susila; Irwan, Siti Nurul Rofiqo (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2026)
Sugar demand is rising with population growth, and although sugar production increased from 2018 to 2022, it has not met national demand. To boost national sugar production, proper fertilizer management is crucial. By calculating and applying compound fertilizer formulations tailored to the specific needs of sugarcane, fertilization efficiency, productivity, and sugar yield can be enhanced. This research aimed to evaluate the performance of morphological characteristics of ratoon sugarcane in response to NPK nutrient management using specific fertilizer formulations. The field study was conducted in Sleman, Special Region of Yogyakarta, from September 2023 to December 2024. The experiment was arranged in a randomized complete block design (RCBD) with three treatments, consisting of NPKSZn (15-15-15-9-0.2) at 400 kg ha⁻¹ + ZA (21N-24S) at 600 kg ha⁻¹ (control); NPKS (14-9-18-4) at 1000 kg ha⁻¹ (Formulation 1); and NPK (23-7-14) at 1000 kg ha⁻¹ (Formulation 2), and four blocks as replications. The collected data were analyzed using Analysis of Variance (ANOVA) at a 5% significance level, followed by the Least Significant Difference (LSD) test at α = 5% to determine the most effective fertilizer formulation. The results showed that the application of these fertilizer formulations significantly affected stalk diameter, millable cane yield and brix content. These findings highlight the importance of synchronized vegetative phase fertilization to optimize ratoon cane growth and support sustainable sugarcane production in Inceptisol soils.